Elements of private international law - Anderson, Winston (The Caribbean Law Publishing Co. Ltd KingstonJM, 2003)
Addresses the means by which Caribbean courts resolve cross-border disputes. Discusses the basic rules governing the exercise of jurisdiction in transnational disputes, the law applied in determining the merits of litigation and the conditions under which foreign judgments will be enforced.